Pengaruh Kualitas Produk Harga dan Citra Merek terhadap Minat Beli pada Tokoh Obat Bawang Merah Desa Monta - Fatmawati; Ita Purnama; Ismunandar (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This study aims to analyze the influence of product quality, price, and brand image on consumer purchase intention at Toko Obat Bawang Merah Desa Monta. The research employed a quantitative approach with an associative research design. Data were collected through questionnaires distributed to 96 respondents selected using purposive sampling. Data analysis was performed using multiple linear regression with the assistance of SPSS version 30.0. The results indicate that, partially, product quality and price have a positive but insignificant effect on purchase intention, whereas brand image has a positive and significant influence. Simultaneously, these three independent variables significantly affect purchase intention, contributing 89.1% to the model, while the remaining 10.9% is influenced by other factors not examined in this study. These findings highlight the importance of building a strong brand image while maintaining product quality and implementing competitive pricing strategies to enhance consumer purchase intention.